Functions of autophagy in plant carbon and nitrogen metabolism - Ren, Chenxia; Liu, Jingfang; Gong, Qingqiu (Frontiers in Plant Science, 2014)
Carbon and nitrogen are essential components for plant growth. Although models of plant carbon and nitrogen metabolisms have long been established, certain gaps remain unfilled, such as how plants are able to maintain a flexible nocturnal starch turnover capacity over various light cycles, or how nitrogen remobilization is achieved during the reproductive growth stage. Recent advances in plant autophagy have shed light on such questions. Not only does autophagy contribute to starch degradation at night, but it participates in the degradation of chloroplast proteins and even chloroplasts after prolonged carbon starvation, thus help maintain the free amino acid pool and provide substrate for respiration. The induction of autophagy under these conditions may involve transcriptional regulation. Large-scale transcriptome analyses revealed that ATG8e belongs to a core carbon signaling response shared by Arabidopsis accessions, and the transcription of Arabidopsis ATG7 is tightly co-regulated with genes functioning in chlorophyll degradation and leaf senescence. In the reproductive phase, autophagy is essential for bulk degradation of leaf proteins, thus contributes to Nitrogen Use Efficiency (NUE) both under normal and low-nitrogen conditions.